Effects of developmental alcohol exposure vs. intubation stress on BDNF and TrkB expression in the hippocampus and frontal cortex of neonatal rats. Issue 43 (21st March 2015) - Boschen, K.E.; Criss, K.J.; Palamarchouk, V.; Roth, T.L.; Klintsova, A.Y.
Abstract: Third trimester‐equivalent alcohol exposure causes significant deficits in hippocampal and cortical neuroplasticity, resulting in alterations to dendritic arborization, hippocampal adult neurogenesis, and performance on learning tasks. The current study investigated the impact of neonatal alcohol exposure (postnatal days 4–9, 5.25 g/kg/day) on expression of brain‐derived neurotrophic factor (BDNF) and the tropomyosin‐related kinase B (TrkB) receptor in the hippocampal and frontal cortex of infant Long–Evans rats. Levels of BDNF protein were increased in the hippocampus, but not frontal cortex, of alcohol‐exposed rats 24 h after the last dose, when compared with undisturbed (but not sham‐intubated) control animals. BDNF protein levels showed a trend toward increase in hippocampus of sham‐intubated animals as well, suggesting an effect of the intubation procedure. TrkB protein was increased in the hippocampus of alcohol‐exposed animals compared to sham‐intubated pups, indicating an alcohol‐specific effect on receptor expression. In addition, expression of bdnf total mRNA in alcohol‐exposed and sham‐intubated pups was enhanced in the hippocampus; however, there was a differential effect of alcohol and intubation stress on exon I‐ and IV‐specific mRNA transcripts. Further, plasma corticosterone was found to be increased in both alcohol‐exposed and sham‐intubated pups compared to undisturbed animals. Upregulation of BDNF could potentially represent a neuroprotective mechanism activated following alcohol exposure or stress. The results suggest that alcohol exposure and stress have both overlapping and unique effects on BDNF, and highlight the need for the stress of intubation to be taken into consideration in studies that implement this route of drug delivery.